Knowledge,attitudes and practices on HIV/AIDS among peer educators in Limpopo Department of Agriculture - Shipalana, Pearl Nkhensani (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology. African Centre for HIV/AIDS Management))--University of Stellenbosch, 2009.